PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN LULUR PURBASARI - Annisa Jannatul Firdausy; Jojok Dwiridotjahjono (Jurnal Pendidikan Ekonomi (JURKAMI), 2022)
This study was intended to examine the effect of price and product quality on customer loyalty through customer satisfaction as an intervening variable (a case study on purbasari scrub customers in Surabaya). The research method used in this research is quantitative. The population in this study were consumers who had purchased and used Purbasari scrub products in the city of Surabaya, using the unknown population formula obtained with a sample of 100 respondents. The measurement scale in this study uses a Likert scale. Collecting research data using a questionnaire. Statistical test and hypothesis testing using path analysis. The results of the study can be concluded that price has a significant effect on customer satisfaction at Purbasari scrubs in Surabaya; Product quality has a significant effect on customer satisfaction at Purbasari scrubs in Surabaya; Price has a significant effect on customer loyalty on Purbasari scrubs in Surabaya; Product quality has a significant effect on customer loyalty on Purbasari scrubs in Surabaya; Customer satisfaction has a significant effect on customer loyalty on Purbasari scrubs in Surabaya; Price has a significant effect on customer loyalty through customer satisfaction as an intervening variable for Purbasari scrub customers in Surabaya; Product quality has a significant effect on customer loyalty through customer satisfaction as an intervening variable for Purbasari scrub customers in Surabaya